Sex-based inequalities in contemporary UK hospital management of stable chest pain - Matthias Schmitt; Michelle Claire Williams; Margaret Loudon; Russel Bull; Stelios Iacovides; Gareth Morgan-Hughes; Carl A Roobottom; Alice Veitch; Franchesca Wotton (Open Heart)
Objective We surveyed UK practice of National Institute for Health and Care Excellence (NICE) “Recent onset chest pain” guidance (CG95, 2016), stratified by sex. We looked for sex-related differences in referral to computed tomographic coronary angiography (CTCA) and subsequent functional imaging (FI), invasive coronary angiography (ICA) and revascularisation.Methods This was a prospective analysis of CTCA practice in 8 UK centres between 2018 and 2020. Coronary artery disease (CAD) was recorded with the CAD-reporting and data system. Local electronic records/archiving/communication systems were used to collect data regarding subsequent FI, ICA and revascularisation.Results 2301 women, 2326 men underwent CTCA; women were older (58±11 vs 55±12 years, p<0.001) but more likely to have normal coronary arteries (46% (1047) vs 29% (685); p<0.001) and less likely to have severe stenosis (7% (169) vs 13% (307); p<0.001). FI was used less for 4% (93) women, 5% (108) men; ICA was also used less for women (8% (182) vs 14% (321)), as was revascularisation (4% (83) vs 8% (177), p<0.001 for all), including those with ≥moderate CTCA stenosis undergoing ICA (53% (79) vs 61% (166); p<0.001).Conclusions Women referred for a NICE CG95 (2016) CTCA are more likely to have normal coronary arteries and men more likely to have CAD. More men than women will then undergo ICA and revascularisation even after adjustments for CTCA disease severity. Raised awareness of these inequalities may improve contemporary chest pain care.